Brand Image, Celebrity Endorser, Packaging: Driving Barenbliss Purchase Intent in Surabaya - Nanda Oktavia; Lia Nirawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Indonesia’s beauty industry is experiencing rapid growth, driven by increasing public awareness of the importance of appearance and skincare. With a population exceeding 270 million, Indonesia holds substantial market potential, particularly among millennials and Generation Z, who are highly receptive to global beauty trends. Globalization has further facilitated access to international beauty products, including those from South Korea. This study aims to examine the influence of brand image, celebrity endorsers, and product packaging on consumers’ purchase intention toward Barenbliss products in Surabaya. A quantitative approach with a relational-causal method was employed. The study involved 217 respondents selected through purposive sampling based on specific criteria: residing in Surabaya, aged 17 years or older, having purchased and used Barenbliss products, and being aware of the brand’s promotional efforts. Data were collected via a structured questionnaire tested for validity and reliability. The data analysis utilized multiple linear regression. The results reveal that brand image, celebrity endorser, and product packaging have a significant simultaneous and partial influence on consumers’ purchase intention for Barenbliss products in Surabaya.